Facilitation of positive social interaction through visual art in dementia: a case study using videoanalysis - Schneider, Justine; Hazel, Spencer; Morgner, Christian; Dening, Tom (Cambridge University Press, 2018)
The aims of this exploratory study were: to investigate the process of visual art appreciation in a person with dementia, in real time; and to test the feasibility of using videoanalysis as a method to explore this process by and with a person who has minimal verbal expression. Gallery personnel guided a woman with severe dementia around an exhibition. Audiovisual recordings of the interactions were analysed. Patterns were identified, and interpreted in the light of Conversation Analysis theory and research. Evidence was found of turn-taking vocalisations on the part of the research participant. Her participation in a dialogical process was facilitated by the skilled and empathic gallery personnel in ways that the analysis makes clear. We argue that this supports the inference that successful communicative acts took place, contrary to expectations in the light of the participant’s level of disability. We demonstrate in this paper how a woman with minimal speech due to dementia was enabled to engage with visual art through the facilitation of an expert guide, attuned to her needs. This is a novel example of a person-centred approach, because it takes place outside the context of caring, which is the typical setting for examining person-centred centred ways of relating to individuals with dementia.